Paediatric cancer stage in population-based cancer registries: the Toronto consensus principles and guidelines. Issue 4 (April 2016) - Gupta, Sumit; Aitken, Joanne F; Bartels, Ute; Brierley, James; Dolendo, Mae; Friedrich, Paola; Fuentes-Alabi, Soad; Garrido, Claudia P; Gatta, Gemma; Gospodarowicz, Mary; Gross, Thomas; Howard, Scott C; et al.
Summary: Population-based cancer registries generate estimates of incidence and survival that are essential for cancer surveillance, research, and control strategies. Although data on cancer stage allow meaningful assessments of changes in cancer incidence and outcomes, stage is not recorded by most population-based cancer registries. The main method of staging adult cancers is the TNM classification. The criteria for staging paediatric cancers, however, vary by diagnosis, have evolved over time, and sometimes vary by cooperative trial group. Consistency in the collection of staging data has therefore been challenging for population-based cancer registries. We assembled key experts and stakeholders (oncologists, cancer registrars, epidemiologists) and used a modified Delphi approach to establish principles for paediatric cancer stage collection. In this Review, we make recommendations on which staging systems should be adopted by population-based cancer registries for the major childhood cancers, including adaptations for low-income countries. Wide adoption of these guidelines in registries will ease international comparative incidence and outcome studies.